2013
DOI: 10.1007/s00107-013-0730-3
|View full text |Cite
|
Sign up to set email alerts
|

Particleboards production from date palm biomass

Abstract: Date palm biomass is a renewable natural resource that has not widely been utilized in industry. The objective of this study was to examine some chemical properties of date palm trunk and rachis (holocellulose, cellulose, lignin and extractives) and to evaluate their suitability to produce composite panels. Particleboards were produced using trunk and rachis as an alternative raw material for forest products industry in the presence of two types of polycondensation resins (phenol-formaldehyde and melamine urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 15 publications
4
21
0
1
Order By: Relevance
“…The higher extractives content of PL may be attributed to its open anatomical structure, which is accessible to the chemicals. These values are close to the values obtained on midribs of five date palm cultivars [7], and on some lignocellulosic residues [36], while they are lower than those reported for date palm trunk (PT) and rachis [11]. There is very little information to compare chemistry of the different parts of date palm residues, but the results found in this work are in partial agreement with previously published studies on non-identified date palm cultivars [17,50].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The higher extractives content of PL may be attributed to its open anatomical structure, which is accessible to the chemicals. These values are close to the values obtained on midribs of five date palm cultivars [7], and on some lignocellulosic residues [36], while they are lower than those reported for date palm trunk (PT) and rachis [11]. There is very little information to compare chemistry of the different parts of date palm residues, but the results found in this work are in partial agreement with previously published studies on non-identified date palm cultivars [17,50].…”
Section: Discussionsupporting
confidence: 91%
“…It can be seen that PT, PFB, FS and DPS had lower cellulose content than typical wood species, while the other parts fall in the range of these wood species. These results are in accordance with the findings of a previous work carried out by Amirou et al [11] on two date palm residues (trunk and rachis) and [7] on the midrib of five date palm cultivars. However, these values are lower than those reported for some lignocellulosic residues [36].…”
Section: Chemical Composition Of the Date Palm Residuessupporting
confidence: 93%
See 2 more Smart Citations
“…Particleboards have been generated using various species of palm trees as the main material such as date palm (Nemli et al 2001;Hegazy and Aref 2010;Amirou et al 2013;Saadaoui et al 2013;Hegazy et al 2015), Washingtonia palm (García-Ortuño et al 2013), and oil palm (Laemsak and Okuma 2000;Hashim et al 2011a;Rasat et al 2011;Suhaly et al 2012;Wad Nadhari et al 2013;Jumhuri et al 2014;Henao et al 2014;Tajuddin et al 2016). The behavior of the particleboard depends on the species of palm tree and the origin of the particles from the trunk or the leaf.…”
Section: Introductionmentioning
confidence: 99%